İş sözleşmesinin işçi tarafından evlilik, askerlik ve sosyal güvenlik hakları nedeniyle feshinde ihbar tazminatı - (:unkn) unknown (My University, 2013)
0
Notice payment in the termination of an employment contract by the employee due to marriage, military service and social security rights
Keywords: Hukuk